2010
DOI: 10.2304/eerj.2010.9.4.444
|View full text |Cite
|
Sign up to set email alerts
|

European Citizenship and European Union Expansion: Perspectives on Europeanness and Citizenship Education from Britain and Turkey

Abstract: This article discusses some perspectives on citizenship education in Turkey and Britain in the context of current contested discourses on the nature of European identity and of the European Union (EU). It is based on data collected during an EU-funded student teacher exchange programme between three universities in Turkey and Leicester University in the United Kingdom. The programme facilitated participants' investigations of their understandings of citizenship and citizenship education in Britain and Turkey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Qualitative data from the open-ended questions in the questionnaire and from the focus groups were analysed thematically. The data and methodology are reported in more detail elsewhere (Wilkins et al, 2010). Given the small number of questionnaire responses from British student teachers training to work in primary schools (p. 27), after careful scrutiny of the data gathered from all the British student teachers (p. 85) showed that generally the views of student teachers training to work in primary and secondary schools (p. 58) were very similar, it was decided to amalgamate the data from the two groups.…”
Section: Methodology and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative data from the open-ended questions in the questionnaire and from the focus groups were analysed thematically. The data and methodology are reported in more detail elsewhere (Wilkins et al, 2010). Given the small number of questionnaire responses from British student teachers training to work in primary schools (p. 27), after careful scrutiny of the data gathered from all the British student teachers (p. 85) showed that generally the views of student teachers training to work in primary and secondary schools (p. 58) were very similar, it was decided to amalgamate the data from the two groups.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…Turkish and British university staff perceived a shared need for academic outcomes (papers, relationships, new research projects) from the exchange programme that arose from the performative policy contexts of higher education in both of their countries. The construction of six joint publications or conference papers Busher, Wilkins, Lawson, Acun & Göz, 2009;Busher, Wilkins, Warwick, Acun & Göz, 2009;Busher et al, 2010a;Busher et al, 2010b;Wilkins et al, 2010) was their response to this performative gaze by their central and institutional governments. However, extensive discussions between participating academics showed up major differences in their preferred research agenda and research approaches, as well as some micro-political barriers to continuing collaboration.…”
Section: University Staff Views On the Impact Of Policy Contexts On Ementioning
confidence: 99%
“…Finding 2 confirms that perceptions of what it means to be European are context-dependent (Table 4). [24,40]. For instance, inhabitants of peripheral and central nations, or continental Europe and the UK, differ in their representations of Europe [5].…”
Section: Synthesis Findingsmentioning
confidence: 99%
“…The seven contributing studies address the importance of cognitive mobilisation [12,32], citizenship education [40], cultural capital oriented to Europe [34], intercultural understanding and comparative education [8,24] to support the development of a relational identification with Europe. Hence, the findings underpin empirically the need for actively incorporating 'Conscious Europeanism' citizenship contents into the existing curricula.…”
Section: Synthesis Findingsmentioning
confidence: 99%
“…Efectivamente, en el proceso de construcción de la identidad europea el impacto que tiene la educación, atendiendo tanto a los aspectos generacionales como a las necesidades evolutivas y a los desafíos y desigualdades políticas y socioeconómicas es fundamental, el carácter socializador que tienen las instituciones educativas (Ortega, 2015) y la cantidad de tiempo que los niños y las niñas, los adolescentes y los jóvenes pasan en ellas representan la piedra angular del motor de cambio social. La importancia de la educación en la configuración de las construcciones sociales, como la identidad, el pluralismo, la democracia y la cohesión social, ha recibido una especial atención en los últimos años tanto por parte de los gobiernos nacionales como por las políticas focales de la Unión Europea (Wilkins, Busher, Lawson, Acun y Göz, 2010), que han incrementado las intervenciones educativas dirigidas a aumentar el compromiso social. Por ejemplo, algunas áreas curriculares específicas para este fin, como la educación para la ciudadanía o la educación para la democracia, han sido estimuladas y financiadas desde la Unión Europea (Ross, 2000).…”
Section: N F O R M a C I ó N D E L A R T í C U L Ounclassified